Behavioral alterations in antibiotic-treated mice associated with gut microbiota dysbiosis: insights from 16S rRNA and metabolomics - Bibi, Asma; Zhang, Famin; Shen, Jilong; Din, Ahmad Ud; Xu, Yuanhong (Frontiers in Neuroscience, 2025)
The gut and brain interact through various metabolic and signaling pathways, each of which influences mental health. Gut dysbiosis caused by antibiotics is a well-known phenomenon that has serious implications for gut microbiota-brain interactions. Although antibiotics disrupt the gut microbiota’s fundamental structure, the mechanisms that modulate the response and their impact on brain function are still unclear. It is imperative to comprehend and investigate crucial regulators and factors that play important roles. We aimed to study the effect of long-term antibiotic-induced disruption of gut microbiota, host metabolomes, and brain function and, particularly, to determine the basic interactions between them by treating the C57BL/6 mice with two different, most commonly used antibiotics, ciprofloxacin and amoxicillin. Anxiety-like behavior was confirmed by the elevated plus-maze test and open field test. Gut microbes and their metabolite profiles in fecal, serum, and brain samples were determined by 16S rRNA sequencing and untargeted metabolomics. In our study, long-term antibiotic treatment exerted anxiety-like effects. The fecal microbiota and metabolite status revealed that the top five genera found were Lactobacillus, Bacteroides, Akkermansia, Ruminococcus_gnavus_group, and unclassified norank_f_Muribaculaceae. The concentration of serotonin, L-Tyrosine, 5-Hydroxy-L-tryptophan, L-Glutamic acid, L-Glutamate, 5-Hydroxyindole acetic acid, and dopaminergic synapsis was comparatively low, while adenosine was high in antibiotic-treated mice. The KEGG enrichment analysis of serum and brain samples showed that amino acid metabolism pathways, such as tryptophan metabolism, threonine metabolism, serotonergic synapsis, methionine metabolism, and neuroactive ligand-receptor interaction, were significantly decreased in antibiotic-treated mice. Our study demonstrates that long-term antibiotic use induces gut dysbiosis and alters metabolic responses, leading to the dysregulation of brain signaling molecules and anxiety-like behavior. These findings highlight the complex interactions between gut microbiota and metabolic functions, providing new insights into the influence of microbial communities on gut-brain communication.